2006
DOI: 10.1128/jb.01044-06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Transcription Activation Exerted by GadX and GadW at the gadA and gadBC Gene Promoters of the Glutamate-Based Acid Resistance System in Escherichia coli

Abstract: In Escherichia coli the gad system protects the cell from the extreme acid stress encountered during transit through the host stomach. The structural genes gadA, gadB, and gadC encode two glutamate decarboxylase isoforms and a glutamate/␥-aminobutyrate (GABA) antiporter, respectively. Glutamate decarboxylation involves both proton consumption and production of GABA, a neutral compound which is finally exported via the GadC antiporter. Regulation of gadA and gadBC transcription is very complex, involving severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 39 publications
3
72
0
Order By: Relevance
“…Metabolic regulation was one of the first bacterial regulatory modalities identified, resulting in thousands of studies addressing all aspects of regulation. This long history of research into metabolic regulation has identified a large number of regulatory proteins capable of responding to changes in the intracellular concentrations of molecules associated with TCA cycle activity, such as NADH (e.g., Rex [4], NmrA [39], and CcpA [21]), citric acid (CcpC [30,33]), glutamate (GadX and GadW [75]), branched-chain amino acids (CodY [61]), and ATP (KinA [69]). These observations lead us to hypothesize that a regulatory protein or proteins respond to TCA cycle-associated metabolites and regulate icaADBC transcription and PIA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic regulation was one of the first bacterial regulatory modalities identified, resulting in thousands of studies addressing all aspects of regulation. This long history of research into metabolic regulation has identified a large number of regulatory proteins capable of responding to changes in the intracellular concentrations of molecules associated with TCA cycle activity, such as NADH (e.g., Rex [4], NmrA [39], and CcpA [21]), citric acid (CcpC [30,33]), glutamate (GadX and GadW [75]), branched-chain amino acids (CodY [61]), and ATP (KinA [69]). These observations lead us to hypothesize that a regulatory protein or proteins respond to TCA cycle-associated metabolites and regulate icaADBC transcription and PIA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many examples of counter-silencing by DNA-binding proteins have been recently described. The AraC-like activators GadX and GadW promote gadA (glutamate decarboxylase) expression, important for acid stress resistance, by antagonizing H-NS [48]. Interestingly, the RNAP-associated protein SspA has been proposed to enhance cell survival at acid pH by reducing hns expression during stationary phase [49].…”
Section: Counter-silencing Of H-ns and Its Functional Consequencesmentioning
confidence: 99%
“…In addition, many other genes which express metabolic enzymes, periplasmic proteins and regulators involved in AR in E. coli have also been examined by microarray and proteomic 2D-gel analyses (Blankenhorn et al, 1999;Tucker et al, 2002). Recently, the Lon protease, endoRNase RNase E and chaperone Hsp31 have been shown to be important in controlling AR systems in E. coli (Heuveling et al, 2008;Mujacic & Baneyx, 2007;Takada et al, 2007), and the roles of AraC-family regulators GadX and GadW and the multidrug resistance regulator MarA in AR systems have also been investigated (Ruiz et al, 2008;Sayed et al, 2007;Tramonti et al, 2006). Nevertheless, despite advances in unravelling some of the regulatory networks involved in AR systems (Foster, 2004;Masuda & Church, 2003), it remains unclear how these factors function together to promote cell survival in low pH conditions.…”
Section: Introductionmentioning
confidence: 99%